Untargeted Metabolite Profiling of Specialty Rice Grains Using Gas Chromatography Mass Spectrometry. (19th September 2022) - Kambale, Rohit; Raveendran, M.; Ramalingam, J.
Abstract : With-ever increasing demand food grains for the increasing population, it has also increased the importance of quality rice with nutritional and therapeutic properties. The quality of rice includes nutritional value, therapeutic properties, and further generation of aroma. Initial studies on sensory analysis using potassium hydroxide (1.7% KOH) identified the presence of a distinct aroma of the traditional rice cultivar Chakhao Amubi in comparison with other aromatic rice varieties were conducted. The metabolomic profiling of aromatic rice grains Chakhao Amubi, Pusa Basmati 1, and nonaromatic rice, Improved White Ponni was attempted to use gas chromatography-mass spectrometry (GC-MS). A total of fifty volatile aromatic compounds, including aromatic hydrocarbons, alkanes, alkenes, ketones, and aromatic aldehydes, have been identified. Detected compounds include six crucial volatile i.e., pentanal, hexanal, 2-pentylfuran, pyridine, (Z)-7-Decenal, and Mesitylene for distinct flavor and presence of aroma in Chakhao Amubi. The findings showed a distinct difference in the metabolic profile of Chakhao Amubi compared to Pusa Basmati 1 and Improved White Ponni. Thus, this study paved the way for a new understanding of the aromatic aspects of traditional rice germplasm and its utilization in rice breeding programs to improve the aroma, therapeutic, and nutritional characteristics of rice.